2005
DOI: 10.1590/s0004-27302005000500019
|View full text |Cite
|
Sign up to set email alerts
|

Tumores endócrinos associados às mutações das proteínas Gsalfa e Gi2alfa

Abstract: Many oncogenic mutations promote tumor growth by inducing autonomous activity of proteins that normally transmit proliferative signal initiated by extracellular factors. G proteins are a family of guanine nucleotide binding proteins, which are structurally homologous and widely distributed in eukaryotic cells. They are composed of three different subunits (alpha, beta e gamma). The alpha subunit, which contains the guanine nucleotide-binding site, is unique to each G protein. The G proteins couple an array of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(72 reference statements)
0
2
1
Order By: Relevance
“…Various studies have demonstrated the prevalence of gsα mutations in GH-secreting pituitary adenomas varies according to geographical location and genetic background of the population (13,7), however, the patient described in the present study demonstrated no mutations in exons 8 and 9 of the gsα gene. Previous studies indicated that the prevalence of gsα mutations in GH-secreting pituitary adenomas varies by the geographical location and the genetic background of the population (7,17).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Various studies have demonstrated the prevalence of gsα mutations in GH-secreting pituitary adenomas varies according to geographical location and genetic background of the population (13,7), however, the patient described in the present study demonstrated no mutations in exons 8 and 9 of the gsα gene. Previous studies indicated that the prevalence of gsα mutations in GH-secreting pituitary adenomas varies by the geographical location and the genetic background of the population (7,17).…”
Section: Discussioncontrasting
confidence: 73%
“…Genetic alterations, such as missense mutations in the gene-encoding α-subunit of G protein (gsα) or the MEN1 gene in multiple endocrinologic neoplasia syndrome 1 (MEN1) have been identified in pituitary adenomas (15). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation